2015
DOI: 10.1039/c5cc02016f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin carbon layer coated MoO2 nanoparticles for high-performance near-infrared photothermal cancer therapy

Abstract: Carbon layer-coated molybdenum dioxide nanoparticles exhibit strong photo-absorption in the near infrared (NIR) region with good photostability. The in vitro and in vivo experiments reveal that an excellent photothermal ablation induced from the nanoparticle agents under NIR irradiation can kill tumor cells not only at the cellular level but also in living organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 27 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…[1][2][3] Nanostructured metal oxide semiconductors with controlled phases and morphologies have been extensively developed for various applications, such as catalysis, 4 energy storage [5][6][7] and biotherapy, 8,9 etc. Currently, metal oxide nanomaterials with oxygen vacancies in their crystal structures, such as WO 3−x 10,11 and MoO 3−x , 12,13 which possess a localized surface plasmon resonance (LSPR) phenomenon have demonstrated strong near-infrared (NIR, 700-1400 nm) absorption. 14 These properties combined with the deep penetration of NIR light through surface tissues makes these materials potentially very effective PTT agents.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Nanostructured metal oxide semiconductors with controlled phases and morphologies have been extensively developed for various applications, such as catalysis, 4 energy storage [5][6][7] and biotherapy, 8,9 etc. Currently, metal oxide nanomaterials with oxygen vacancies in their crystal structures, such as WO 3−x 10,11 and MoO 3−x , 12,13 which possess a localized surface plasmon resonance (LSPR) phenomenon have demonstrated strong near-infrared (NIR, 700-1400 nm) absorption. 14 These properties combined with the deep penetration of NIR light through surface tissues makes these materials potentially very effective PTT agents.…”
mentioning
confidence: 99%
“…15,16 The MoO 3−x nanostructures have shown promising applications especially when used as PTT agents due to their relatively low cost, mild synthesis, excellent photothermal performance and low toxicity. 12,13,17 Remarkable achievements have been made for MoO 3−x around biomedical applications, especially as PTT agents, but there remain prominent challenges such as materials synthesis procedures, size-controlled MoO 3−x nanostructures and improvement of photothermal performance. 13,18 Facile fabrication of MoO 3−x nanostructures was first realized by Song et al 17 They showed that complicated post treatments of hydrophobic and less biocompatible oleylamine molecules coated nanomaterials could be avoided.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MoO 2 is a wide-band gap semiconductor with metallic electronic property, which has a wide applications in field emission, 21,22 supercapacitors, 23,24 lithium ion batteries, 25,26 cataly, 27,28 biosensing, 29 etc. Up to now, all kinds of MoO 2 and its composite nanostructure such as nanowire, 22 nanorod, 23,24 nanostar, 21 nanosphere, 25 nanoparticle, 27,29 MoS 2 /MoO 2 plate, 30 and MoO 2 /C nanosheet have been fabricated. 26 However, very few papers reported on monodispersity of ultrathin MoO 2 nanosheets.…”
mentioning
confidence: 99%
“…16) have become popular because they are inexpensive and readily available. However, some researchers have reported that the potential toxicity, 17 undegradability, 18 and low hemolytic activity 16 impair their application in biomedicine to some extent. Although Fe 3 O 4 nanoparticles could avoid these problems and effectively absorb NIR light, and have been clinically applied in hyperthermia cancer therapy using NIR, 19 poor dispersion stability and easy aggregation usually lead to low activity of Fe 3 O 4 nanoparticles.…”
Section: Nirmentioning
confidence: 99%